Analysis of the Effect of Sizing Add-on% and Sizing Process Parameters on the Average Warp Breakage Rate for 30Ne 100% Cotton Warp Yarn - Jahangir, Dutimoyi; Hossain, Md Shakhawat (Journal of Engineering Science, 2023)
Sizing is one of the essential steps in fabric manufacturing for increasing weaving production efficiency in the case of cotton and cotton blend fabrics by providing a protective coating to warp yarn that does not add any functional value. This research aimed to analyze the effects of size add-on% and two sizing process parameters, such as sizing machine speed and squeezing roller pressure, on the average warp yarn breakage rate during weaving. The sizing experiments have been conducted based on the size add-on% (8.93 %, 9.94%, 11.23%), sizing machine speed (35 yards/min, 38 yards/min, 40 yards/min), and squeezing roller pressure (2.2 kg, 3.3 kg, 3.5 kg) on the 30Ne 100% cotton warp yarn. It was found from the experimental results that the warp yarn breakage rate was increased with the rise in sizing machine speed and squeezing roller pressure. In contrast, the lowest warp yarn breakage rate was exhibited in size add-on% 9.94 in the loom during weaving. Based on the research, promising industrial application is highlighted for future fabric production. Journal of Engineering Science 13(2), 2022, 111-115